Facile synthesis of MoO2 nanoparticles as high performance supercapacitor electrodes and photocatalysts. Issue 2 (1st February 2016) - Zhou, E.; Wang, Chenggang; Zhao, Qinqin; Li, Zhipeng; Shao, Minghui; Deng, Xiaolong; Liu, Xiaojing; Xu, Xijin
Abstract: Molybdenum dioxide (MoO2 ) nanoparticles with the size of 200 nm in diameter were synthesized by a facile hydrothermal method. The nanoparticles were directly functionalized as supercapacitors (SCs) electrodes and photocatalysts. The electrochemical studies showed that the SCs demonstrated high capacitance of 621 F g −1, which was 3 times larger than previous reports. Furthermore, they exhibited good cyclic performance with 90% capacity retention after 1000 cycles at a current density of 1 A g −1 . The photocatalytic activities were evaluated by the degradation of methylene blue (MB) and rhodamine B (RhB), respectively, and the nanoparticles demonstrated preferred selectivity on the degradation of RhB (70%) than that of MB (30%).